STUDY ON OBESITY AND OVERWEIGHT AMONG CHILDREN IN THE PRIMARY CYCLE AT NATIONAL PLAN - Cojocaru Daniela (Editura Univeristatii "Stefan cel Mare" din Suceava, 2021)
Prevention of childhood obesity is a public health issue and requires close monitoring of those with a tendency to gain weight. Most researchers believe that obesity that has appeared since childhood and is maintained until adolescence is much more difficult to treat. Obesity among children inevitably decreases life expectancy. The problem of overweight and excessive growth of obesity since childhood it can be prevented or slowed down by implementing diversified programs if society focuses more on the causes. There are many causes, some more crucial than others, but through a balanced diet, combined with systematic physical activity, it can prevent obesity and overweight in all children around the world. [7] Next, I will present the studies done at the national level regarding the presence of obesity and overweight in children aged 6-19 years.